Sistem Pendukung Keputusan Pemberian Kredit Koperasi Menggunakan Metode Weighted Product - Supiyandi Supiyandi; Raja Nasrul Fuad; Eko Hariyanto; Satia Larasati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Credit is a major part of financing economic activity. Credit is an important activity for cooperatives, because credit is a source of funds for cooperatives. Prior to commencement of lending activities, a good and thorough analysis is needed of all aspects of credit that can support the credit granting process, in order to prevent credit risks and irregularities, one of which is bad credit. Therefore it is necessary to have a system that can support decision making in providing credit. With the decision support system created, it is hoped that it can help the chairman of the cooperative in analyzing credit and reducing the level of bad credit in the cooperative. In the assessment, a good mechanism is needed, one of which can be done by using the weighted product (WP) method. The weighted product (WP) method uses multiplication to relate the attribute rating, where each attribute rating must first be ranked with the attribute weight in question. From the end result of the research conducted for the provision of credit is whether or not cooperative members deserve credit.